A study on factors contribute toward the effectiveness of composting food waste policy among residents at Hulu Selangor / Norlela Sari Misri and Nurasykin Nor’azman - Misri, Norlela Sari; Nor’azman, Nurasykin (2022)
This study investigates the factors contribute towards the effectiveness of composting food waste policy among residents at Hulu Selangor. This research used a convenience sampling involving 300 respondents from various layers of society. This research is intended to establish the vital relationship between independent variables and dependent variables. This study indicates that stakeholder engagement, active implementation and transparency have an important relationship with effectiveness of composting food waste policy among residents at Hulu Selangor. In this study, the survey was given to Hulu Selangor residents. Online questionnaire was used to provide the researcher with a successful insight into the issue. This study concludes that the stakeholder engagement, active implementation and transparency contribute towards the effectiveness of composting food waste policy among residents at Hulu Selangor.